High altitude pulmonary edema at 2640 m altitude associated with an acute Rhinovirus infection. First case in the literature - Diego Alejandro Cubides Diaz; Natalia Muñoz Angulo; Luz Adriana Herrera Alzate; Daniel Martin Arsanios; Ana Lucía Ovalle Monroy; Omar Velandia; Carlos Mauricio Calderón Vargas (Respiratory Medicine Case Reports, 2023)
High altitude pulmonary edema (HAPE) is a multifactorial condition that may occur after ascent of high altitudes, especially in genetic predisposed individuals. Diagnosis is challenging and could lead to potentially lethal complications such as acute respiratory distress syndrome (ARDS). We present one of the few reported cases of HAPE below 3000 m of altitude, and the first to our knowledge to present with a concomitant acute Rhinovirus infection, precipitating and complicating the diagnosis and clinical course. Clinical manifestations, treatment, and outcomes are shown below.